2023
DOI: 10.3390/nano13152263
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Optical Properties of Oxidized Graphenes

Talia Tene,
Paola G. Vinueza-Naranjo,
Yesenia Cevallos
et al.

Abstract: In this study, we investigate how changing important synthesis-related parameters can affect and control the optical characteristics of graphene oxide (GO) and reduced graphene oxide (rGO). These parameters include drying time and reduction time at two different temperatures. We obtain an understanding of their impact on optical transitions, optical bandgap, absorption coefficient, and absorbance spectrum width by analyzing these factors. Accordingly, GO has an optical bandgap of about 4 eV, which is decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…To further emphasize our eco-friendly approach, previous studies ( Begum et al, 2017 ; Tene et al, 2022b ; Tene et al, 2022c ) have shown that GO can be transformed into rGO using green reducing agents such as citric acid (CA) ( Tene et al, 2023b ). In our current study, we specifically focus on GO reduced using AA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further emphasize our eco-friendly approach, previous studies ( Begum et al, 2017 ; Tene et al, 2022b ; Tene et al, 2022c ) have shown that GO can be transformed into rGO using green reducing agents such as citric acid (CA) ( Tene et al, 2023b ). In our current study, we specifically focus on GO reduced using AA.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we provide a brief description of the synthesis of GO and rGO, which is depicted in Schematic S1. Our prior works and associated applications ( Tene et al, 2020 ; Tene et al, 2022b ; Tene et al, 2023a ; Tene et al, 2023b ) contain more comprehensive information regarding the full synthesis process. Furthermore, for a meaningful comparison with the present work involving other environmentally friendly reducing agents, please refer to Ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation